Some ideas around "A taberna do Galo" of Celso Emilio Ferreiro - García López, José Ángel (Madrygal. Revista de Estudios Gallegos, 2012)
This essay deals with an approachment to some aspects relative to the narrative instances, intertextuality and some references taken from reality (recognized or not by the experts) that we observe in the book A taberna do Galo, one of the latest writings of Celso Emilio Ferreiro, which saw the light in 1978 in advance of an original that this author did not arrive to conclude: Memorias de nunca.